If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 93 = 6 + 3x Solving 93 = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 93 + -3x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 93 + -3x = 6 + 0 93 + -3x = 6 Add '-93' to each side of the equation. 93 + -93 + -3x = 6 + -93 Combine like terms: 93 + -93 = 0 0 + -3x = 6 + -93 -3x = 6 + -93 Combine like terms: 6 + -93 = -87 -3x = -87 Divide each side by '-3'. x = 29 Simplifying x = 29
| 1-3(8x-1)=-6x+40 | | Y-8x=24 | | 270T+109=530-60t | | -52=4m+6-7m-19 | | -3x=-8+2y | | .11111111(x^2)=30 | | 12x-3+6x+3=180 | | v*9=72 | | 6(x-3)=2(x+8) | | 375000=x-(x*.32) | | 2x=5x-9x+18 | | 15+(m-2)=4 | | 5(2k-6)+7=8k-4 | | 2x^2+11x=2x+35 | | x+8=4r-4 | | (X-6)(y+6.6)=308 | | 14+4r-5r=3r-6 | | 2x^2=3x^2+9 | | -x^3+76x+240=0 | | 2x^2+20x=-18 | | 2.7t+1.09=5.3-.6t | | 12x-45=180 | | 0.5n+2n=20 | | -y+7x=-4 | | -1x+2=-2+-1x | | 3n-n=7n+11 | | 3x^2-36=3x^2-8x+4 | | 7x+4+16x-8=180 | | 10.3*7.8= | | 180-12x=45 | | x+8y=40-x | | 10x+15=6x+13 |